DEVELOPMENT AND STATISTICAL OPTIMIZATION OF GASTRORETANTIVE FLOATING MICROSPHERES OF PREGABALIN PREPARED BY W/O/O MULTIPLE EMULSION METHOD - KHARB, MONIKA; TANWAR, Y. S. (International Journal of Applied Pharmaceutics, 2021)
Objective: The aim of this study is to develop a gastroretentive microsphere of pregabalin using design of experiment (DoE) to decrease dosing frequency and increasing bioavailability. Methods: Pregabalin microsphere was prepared by W/O/O multiple emulsion method using a mixture of ethyl cellulose (EC) and polyvinyl pyrrolidone (PVP) as rate-controlling polymer. Mixed solvent system comprising of dichloromethane (DCM) and acetonitrile (ACN) and light liquid paraffin was chosen as primary and secondary oil phase respectively. Taguchi design was employed for factor screening and Box Behnken design was used for the optimisation of critical process parameters. Results: Taguchi design revealed that polymer: drug, DCM: ACN and PVP: EC is the critical factor for the preparation of microspheres. The optimized formulation was prepared using polymer: drug (4.95:1), DCM: ACN (53.76: 46.24) and PVP: EC (2:5) which showed mean particle size of 203.34±4.82 µm, practical yield of 87.52±2.91 %, encapsulation efficiency of 96.43±3.14 %, floating ability up to 90.42±1.64 % and T60% of 332.81±5.84. Drug release from microsphere followed Higuchi Kinetic model. Conclusion: In a nutshell, microspheres with excellent flowability and great encapsulation efficiency were successfully developed. These can be useful in improving patient compliance by reducing frequent dosing.